1999
DOI: 10.1115/1.2825922
|View full text |Cite
|
Sign up to set email alerts
|

Flat Miniature Heat Pipes With Micro Capillary Grooves

Abstract: Flat miniature heat pipes (FMHP’s) are shown to be very promising in the cooling of electronic component systems. This investigation presents a detailed experimental and theoretical analysis on maximum heat transfer capabilities of two copper-water FMHP’s with diagonal trapezoidal micro capillary grooves and one copper-water FMHP with axial rectangular micro capillary grooves. Maximum heat flux on the evaporator wall of the 120-mm long axial grooved heat pipe, with a vapor channel cross-sectional area of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(98 citation statements)
references
References 6 publications
3
94
0
1
Order By: Relevance
“…An overview was presented elsewhere for the development of the micro heat pipe [52]. The fabrication and experimental data on the performance characteristics of the flat water-copper heat pipe with external dimensions 2 × 7 × 120 mm have been reported with radial heat fluxes of 90 W/cm 2 and 150 W/cm 2 for horizontal and vertical applications, respectively [53]. Reference [54] studied the heat transfer limitation of the micro heat pipe and found that the maximum heat-transport capacity of a micro heat pipe depends upon the capillary and fluid continuum limit.…”
Section: Micro Heat Pipementioning
confidence: 99%
“…An overview was presented elsewhere for the development of the micro heat pipe [52]. The fabrication and experimental data on the performance characteristics of the flat water-copper heat pipe with external dimensions 2 × 7 × 120 mm have been reported with radial heat fluxes of 90 W/cm 2 and 150 W/cm 2 for horizontal and vertical applications, respectively [53]. Reference [54] studied the heat transfer limitation of the micro heat pipe and found that the maximum heat-transport capacity of a micro heat pipe depends upon the capillary and fluid continuum limit.…”
Section: Micro Heat Pipementioning
confidence: 99%
“…It can be seen from this overview that three types of grooved metallic FMHP are developed: i. Type I: FMHPs with only axial rectangular, triangular or trapezoidal grooves (Murakami et al, 1987;Plesh et al, 1991;Sun and Wang, 1994;Ogushi and Yamanaka., 1994;Cao et al, 1997;Hopkins et al, 1999;Schneider et al, 1999aSchneider et al, , 1999bSchneider et al, , 2000Avenas et al, 2001, Cao and Gao, 2002, Lin et al, 2002Chien et al, 2003;Moon et al, 2003Moon et al, , 2004Soo Yong and Joon Hong, 2003;Lin et al, 2004;Romestant et al, 2004;Zhang et al, 2004;Popova et al, 2006;Lefevre et al, 2008;Lim et al, 2008;Tao et al, 2008, Zhang et al, 2009Xiaowu et al, 2009). These FMHPs allow for high heat fluxes for horizontal or thermosyphon positions (up to 150 W/cm²).…”
Section: Literature Survey On Mini Heat Pipes Prototyping and Testingmentioning
confidence: 99%
“…The fabrication of narrow grooves with sharp corner angle is a challenging task for conventional micromachining techniques such as precision mechanical machining. Accordingly, a number of different techniques including high speed dicing and rolling method (Hopkins et al, 1999), Electric-Discharge-Machining (EDM) (Cao et al, 1997;Cao and Gao, 2002;Lin et al, 2002), CNC milling process (Cao and Gao, 2002;Gao and Cao, 2003;Lin et al, 2004;Sarno, 2001, Zaghdoudi et al, 2004;Lefèvre et al, 2008), drawing and extrusion processes (Moon et al, 2003(Moon et al, , 2004Romestant et al, 2004;Xiaowu, 2009), metal forming process (Schneider et al, 1999a(Schneider et al, , 1999b(Schneider et al, , 2000Chien et al, 2003), and flattening (Tao et al, 2008) have been applied to the fabrication of microgrooves.…”
Section: Literature Survey On Mini Heat Pipes Prototyping and Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle decreases until the minimum meniscus contact angle φ 0 for the particular solid-liquid combination is reached. Past this point, the meniscus detaches from the top of the groove and recedes into the groove (Hopkins et al [19]). When the meniscus reaches the fillet region of the groove, the cross-sectional area decreases dramatically for small changes in the height of the meniscus attachment point due to the requirement that the contact angle must remain constant, as shown in Fig.…”
Section: B Effect Of Groove Fill Amountmentioning
confidence: 99%